2023
DOI: 10.3390/en16134857
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Various Dusts and Humidity on the Performance of Renewable Energy Modules

Abstract: Due to the depletion of fossil fuels, cost-effective and efficient alternate energy resources are a major topic of research nowadays. Solar energy is one of the renewable energy sources which is under research. The main emphasis is on developing new technologies for harnessing the sun’s energy efficiently. Solar photovoltaic (PV) cells are one such technology that works on the principle of the photovoltaic effect, with the electric output generated by it being directly influenced by the amount of light reachin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…A comparison of results shows that a maximum temperature drop, i.e., 50 K and 60 K, is achieved at 0.5 LPM and 0.525 LPM for the mini-channel heat sink, respectively. Gong et al [ 40 ] numerically investigated the thermal management of electronic devices for different layouts of the micro-channel heat sink. Their research revealed that the minimum pressure drop achieved in the different layouts was nearly 250 Pa at 0.09 LPM compared to the pressure drop of 130 Pa at 0.525 LPM in this investigation.…”
Section: Experimental Validationmentioning
confidence: 99%
“…A comparison of results shows that a maximum temperature drop, i.e., 50 K and 60 K, is achieved at 0.5 LPM and 0.525 LPM for the mini-channel heat sink, respectively. Gong et al [ 40 ] numerically investigated the thermal management of electronic devices for different layouts of the micro-channel heat sink. Their research revealed that the minimum pressure drop achieved in the different layouts was nearly 250 Pa at 0.09 LPM compared to the pressure drop of 130 Pa at 0.525 LPM in this investigation.…”
Section: Experimental Validationmentioning
confidence: 99%